Bidirectional effects of IL-10+ regulatory B cells in Ldlr−/− mice. (January 2019) - Douna, Hidde; Amersfoort, Jacob; Schaftenaar, Frank H.; Kroon, Sanne; van Puijvelde, Gijs H.M.; Kuiper, Johan; Foks, Amanda C.
Abstract: Background and aims: Limiting the pro-inflammatory immune response is critical for the treatment of atherosclerosis. Regulatory B cells (Bregs) can modulate the immune response through interleukin-10 (IL-10). Current data regarding Bregs and atherosclerosis is scarce and conflicting. Methods: In this study, we investigated the frequency of IL-10 + B cells during the development of atherosclerosis in low-density lipoprotein receptor-deficient ( Ldlr −/− ) mice and studied the effect of adoptive transfer of IL-10 + B cells on atherosclerosis. Results: We found a very strong inverse correlation between atherosclerosis severity and the frequency of IL-10 + B cells. This effect was cholesterol-independent and observed in spleen, draining lymph nodes and peritoneal cavity. To directly assess the effects of IL-10 + B cells on atherosclerosis, we expanded IL-10 + B cells ex vivo with anti-CD40 and selected pure and viable IL-10-secreting B cells and IL-10 - B cells and adoptively transferred them to Ldlr −/− mice, respectively. While IL-10 - B cells were strongly atherogenic compared to control-treated mice, IL-10 + B cells did not affect lesion size. Adoptive transfer of IL-10 + B cells strongly reduced circulating leukocyte numbers and inflammatory monocytes. In addition, they decreased CD4 + T cell activation and increased IL-10 + CD4 + T cell numbers. Interestingly, both IL-10 + and IL-10 - B cells exacerbated serum cholesterol levels and resulted in fatty livers, which potentially masked the beneficial effects of IL-10 + B cells on atherosclerosis. Conclusions: These findings underscore the strong immune-regulating function of IL-10 + B cells and provide additional incentives to explore effective strategies that expand IL-10 + B cells in atherosclerosis. Graphical abstract: Highlights: IL-10 + B cells are drastically reduced in Ldlr −/− mice on Western type diet. IL-10 + B cells are inversely correlated with atherosclerosis severity. IL-10 +, but not IL-10 -, B cells strongly regulate the immune system in vivo. IL-10 - B cells are atherogenic, while IL-10 + B cells do not affect lesion formation. The protective effects of IL-10 + B cells may be masked by increased cholesterol.